Black Labor Migration in Caribbean Guatemala, 1882-1923 - Opie, Frederick Douglass (Book collections on Project MUSE., 2009)
Using primary and secondary sources as well as ethnographic data, Opie details the struggles of these workers who were ultimately inspired to organize by the ideas of Marcus Garvey. Regularly suffering class- and race-based attacks and persecution, black labourers frequently met such attacks with resistance. Their leverage - being able to shut down the railroad - was crucially important to the revolutionary movements in 1897 and 1920.